PENINGKATAN SKILL PESERTA DIDIK MELALUI PENGENALAN DATABASE DI PKBM RISTEK NUSANTARA JAYA JAKARTA - Iis Kartini; Setiawan Setiawan; May Vitha Rahmadhani; Fatimah Malini Lubis; Ary Bayu Nugraha (POLITEKNIK LP3I JAKARTA, 2021)
The implementation of improving student skills through the introduction of databases at PKBM Research and Technology Nusantara Jaya Jakarta went as expected. This activity is located at PKBM Research and Technology Nusantara Jaya Raya Jakarta on September 11, 2021. The stages in this activity are identifying needs/problems, making alternative decisions, making decisions, implementing decisions, and evaluating implementation. In the implementation of the implementation, some students still did not understand the themes discussed, but were given intense and exclusive assistance during the training so that all students could understand the material provided from beginning to end. The importance of increasing student skills through the introduction of databases at PKBM Research and Technology Nusantara Jaya to facilitate students to recognize and understand the use of databases for both individual and group interests and to improve skills for students.Keywords: PKBM, Skill enhancement, database introduction